Famílias pós-modernas e seus desafios à pastoral familiar - Holanda, Francimilson Gonçalves de (2011)
The research concerns itself with answering up to what point can Family Ministry offer alternatives to the challenges of the post modern culture. Toward this end it sought first to present the models of families present in the Sacred Bible, these families which were also marked by frailties just like current families. Without losing sight of the Catholic Christian focus, the investigation invests in the nuclear and monogamous model of matrimony emphasizing the indissolubility and fidelity between the marital couple alongside the Christian education of the children. Amid the circumstances of post modernity, which give rise to new family configurations, the Church feels itself challenged to continue its prophetic mission, announcing with conviction that the Christian Family continues to be a sanctuary of life and of the domestic church, witnessing the love of Christ to the world through a home filled with love and comprehension so that the children, as they become adults, may intervene in a solidary and fraternal way in the social environment, constructing the civilization of love.